STRATEGI KOMUNIKASI BIRO INFORMASI PERTAHANAN KEMENTERIAN PERTAHANAN DALAM MEMPERKENALKAN LORONG SEJARAH SEBAGAI WISATA EDUKASI PERTAHANAN - Narendra Prema Dwi Ekananda; Flora Meliana Siahaan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The increasing mobility of domestic tourism and the rapid growth of digital penetration in Indonesia have encouraged the Ministry of Defense to launch the Lorong Sejarah (History Corridor) program as a defense education tourism initiative. Consequently, an appropriate public communication strategy is required to ensure that historical messages and national values are effectively conveyed to the broader community. This study employs Lasswell’s communication model and Cangara’s communication strategy framework, which consists of the stages of research, planning, implementation, evaluation, and reporting, as its theoretical foundation, supported by public relations concepts to examine the role of the Defense Information Bureau. A descriptive qualitative approach was adopted, with data collected through in depth interviews, observation, and documentation involving five informants. The data were processed through data verification, categorization, simplification, and narrative organization, and subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña. The trustworthiness of the findings was ensured through source and technique triangulation. The results indicate that the research and planning stages were conducted adequately with clear audience segmentation, while the implementation stage integrated face to face and digital communication channels in a complementary manner. However, the evaluation and reporting stages remained anecdotal and lacked systematic measurement. All five elements of Lasswell’s communication model were identified, generating cognitive, affective, and conative effects among visitors. Nevertheless, several challenges persist, including limited resources, the absence of formal written policy guidelines, and the need to improve message relevance for younger generations. This study concludes that the communication strategy implemented by the Defense Information Bureau has been effective at the micro level but requires stronger institutional support at the macro level.